METODE PENAFSIRAN HUKUM SEBAGAI ALAT MENCARI KEADILAN HAKIKI - Hasibuan, H. A. Lawali; Nst, Alvin Hamzah (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2023)
The method of legal interpretation has a crucial role in seeking ultimate justice in the legal system. True justice is an essential principle in maintaining a balance between legal norms and moral values and community justice. This paper discusses how the method of legal interpretation serves as a tool to achieve ultimate justice. The method of legal interpretation is an analytical approach used by legal experts to understande and apply legal norms to concrete situations. Legal interpretations can be diverse, such as textual, historical, systematic, and teleological, each of which has its own focus on reading and applying law. In the context of seeking ultimate justice, these methods must be used holistically and in a balanced manner